2010
DOI: 10.1093/toxsci/kfq083
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Regulates Response to Pesticides in Drosophila via Conserved Pdp1 Pathway

Abstract: Daily rhythms generated by the circadian clock regulate many life functions, including responses to xenobiotic compounds. In Drosophila melanogaster, the circadian clock consists of positive elements encoded by cycle (cyc) and Clock (Clk) and negative elements encoded by period (per) and timeless (tim) genes. The epsilon-isoform of the PAR-domain protein 1 (Pdp1epsilon) transcription factor is controlled by positive clock elements and regulates daily locomotor activity rhythms. Pdp1 target genes have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Circadian clocks are involved in the regulation of response to genotoxic stress and xenobiotics in both mice and fly (Antoch et al, 2008; Beaver et al, 2010; Gachon and Firsov, 2011). Therefore, increased neurodegeneration in arrhythmic sni 1 and sws 1 mutants may involve additional pathways beyond ROS homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian clocks are involved in the regulation of response to genotoxic stress and xenobiotics in both mice and fly (Antoch et al, 2008; Beaver et al, 2010; Gachon and Firsov, 2011). Therefore, increased neurodegeneration in arrhythmic sni 1 and sws 1 mutants may involve additional pathways beyond ROS homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…123,124) There are also data showing coordinate control of some esterase, P450 and GST genes mediated by circadian clock genes, with correlated effects on xenobiotic (including permethrin) detoxification. [124][125][126] It is clearly unlikely that circadian clock genes are directly involved in the resistance phenotypes we have reviewed. However these and the microarray data demonstrate that the expression of at least some genes with primary detoxification functions are embedded in larger regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…However these and the microarray data demonstrate that the expression of at least some genes with primary detoxification functions are embedded in larger regulatory networks. Orthologues of the genes encoding transcription factors or receptors downstream of the Drosophila clock genes in the pathway which Beaver et al 125) have begun to elucidate may be candidate loci for the master regulator mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Since metabolic resistance of insecticides is believed to develop through upregulation of detoxification pathways [40], [44], the time of day when expression of detoxification genes and subsequent enzyme activities is at their minimum may correspond to the time when insects are most susceptible to insecticides. A study using D. melanogaster as a model concluded that there is indeed some correlation between the circadian timing of susceptibility to certain classes of pesticides to expression of circadian regulated Phase I and II detoxification enzymes [45], [46]. Assuming that detoxification of xenobiotics in D. suzukii is similar to that in D. melanogaster , other insects, and even mammals [46][49] in being under circadian clock control, it may be possible to identify a time period when D. suzukii is most susceptible to insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…A study using D. melanogaster as a model concluded that there is indeed some correlation between the circadian timing of susceptibility to certain classes of pesticides to expression of circadian regulated Phase I and II detoxification enzymes [45], [46]. Assuming that detoxification of xenobiotics in D. suzukii is similar to that in D. melanogaster , other insects, and even mammals [46][49] in being under circadian clock control, it may be possible to identify a time period when D. suzukii is most susceptible to insecticides.…”
Section: Introductionmentioning
confidence: 99%